Case Report: Isolated Cystic Dilatation of the Cystic Duct: A Misdiagnosed Case Preoperatively - Zhang, Jiankang; Hu, Zeming; Lin, Xuan; Zhang, Dongliang; Wang, Hao; Chen, Bin (Frontiers in Surgery, 2021)
A 33-year-old female with mild elevation of liver transaminase was sent to the general surgery department for medical services due to right upper abdominal pain for 2 weeks. A liquid dark area approximately 4cm×3cm×3cm in size in the theoretical location of the pancreatic segment of the common bile duct was detected by abdominal computed tomography (CT); no enhancement of the cystic wall was found in the enhanced CT scan; and then the patient was diagnosed with choledochal cyst based on the results of the radiological images preoperatively. During the operation, the isolated cystic dilatation was found at the middle part of the cystic duct, and its caudal portion was found behind the head of the pancreas and converged into the common bile duct at an acute angle and low insertion. According to the intraoperative evaluation, the female was diagnosed with a cystic duct cyst (CDC). The surgery was converted to laparotomy for the unclear structure and the possibility of anatomic variation of the bile duct. The caudal portion of the cystic duct was found communicated with the common bile duct with a narrow base, and the extra hepatic bile duct was not cystic. The CDC was removed in the surgery. One week later, the patient was discharged from the hospital for the disappearance of abdominal pain and normal liver transaminase who did not suffer from any discomfort in the one-month-long follow-up. The lessons drawn from this case were as follows: (1) The distinction between the relatively frequent choledochal cyst and the isolated CDC should always be taken in mind; (2) Surgical strategy should be given priority for intraoperatively confirmed CDC; (3) Common bile duct exploration is recommended for patients with choledocholithiasis or jaundice.